Strategi Keterlibatan Guru Dalam Menanamkan Karakter Disiplin Dan Tanggung Jawab Peserta Didik Kelas III di SDN Pataruman Cianjur - Muhammad Ramanda Isky; Dera Nugraha; Alfa Rohmatin (PT. Nawa Edukasi Nusantara, 2026)
Character education in elementary schools requires direct teacher involvement because students are still in the stage of forming learning habits and social behavior. This study aims to examine teacher involvement strategies in instilling discipline and responsibility among third-grade students at SDN Pataruman Cianjur. This research used a qualitative descriptive approach. Data were collected through observation, interviews, and documentation involving the third-grade teacher, the principal, and students. The data were analyzed through data reduction, data presentation, and conclusion drawing, while data validity was strengthened through source and technique triangulation. The findings show that teacher involvement was carried out through exemplary behavior, daily habituation, classroom rules, task assignment, direct supervision, positive reinforcement, and educative verbal reminders. Discipline was developed through punctuality, classroom order, compliance with learning instructions, and consistency in following school rules. Responsibility was developed through completing assignments, bringing learning equipment, maintaining classroom cleanliness, and carrying out simple classroom roles. The study concludes that discipline and responsibility can be strengthened when teachers consistently connect character values with daily classroom practices. This research contributes to a more specific understanding of character education by focusing on two core values in elementary learning behavior.